PERMAINAN KOTAK MINI ZOO SEBAGAI MEDIA STIMULASI PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN - Cholid, Abd; Nurul Affrida, Ervin (incrementapedia, 2021)
Early childhood who are in the golden period of development need proper stimulation in learning. The stimulation uses media in the form of educational game tools. Gross motor stimulation of children aged 4-5 years can be used in various methods, one of which is using the Zoo's Little Box game.